Joint and Muscle Assessments of the Separate Effects of Botulinum NeuroToxin-A and Lower-Leg Casting in Children With Cerebral Palsy - Peeters, Nicky; Van Campenhout, Anja; Hanssen, Britta; Cenni, Francesco; Schless, Simon-Henri; Van den Broeck, Christine; Desloovere, Kaat; Bar-On, Lynn (Frontiers in Neurology, 2020)
Botulinum NeuroToxin-A (BoNT-A) injections to the medial gastrocnemius (MG) and lower-leg casts are commonly combined to treat ankle equinus in children with spastic cerebral palsy (CP). However, the decomposed treatment effects on muscle or tendon structure,stretch reflexes and joint , are unknown. In this study, BoNT-A injections to the MG and casting of the lower legs were applied separately to gain insight into the working mechanisms of the isolated treatments on joint, muscle and tendon levels. Thirty-one children with spastic CP (GMFCS I-III, age 7.4 ± 2.6 years) received either two weeks of lower-leg casts or MG BoNT-A injections. During full range of motion slow and fast passive ankle rotations, joint resistance and MG stretch reflexes were measured. MG muscle and tendon lengths were assessed at resting and at maximum dorsiflexion ankle angles using 3D-freehand ultrasound. Treatment effects were compared using non-parametric statistics. Associations between the effects on joint and muscle or tendon levels were performed using Spearman correlation coefficients (p<0.05). Increased joint resistance, measured during slow ankle rotations, was not significantly reduced after either treatment. Additional joint resistance assessed during fast rotations only reduced in the BoNT-A group (-37.6%, p=0.013, effect size=0.47), accompanied by a reduction in MG stretch reflex (-70.7%, p=0.003, effect size=0.56). BoNT-A increased the muscle length measured at the resting ankle angle (6.9%, p=0.013, effect size=0.53). Joint angles shifted towards greater dorsiflexion after casting (32.4%, p=0.004, effect size=0.56), accompanied by increases in tendon length (5.7%, p=0.039, effect size=0.57; r=0.40). No associations between the changes in muscle or tendon morphology and the changes in the stretch reflexes were found. Intramuscular BoNT-A injections reduced stretch reflexes in the MG accompanied by an increase in resting muscle belly length, whereas casting resulted in increased dorsiflexion without any changes to the muscle length. This supports the need for further investigation on the effect of the combined treatments and the development of treatments that more effectively lengthen the muscle.